2016
DOI: 10.1200/jco.2016.67.4044
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Cancer: The Role of Pharmacotherapy

Abstract: Type 2 diabetes mellitus (T2DM) is becoming increasingly prevalent worldwide. Epidemiologic data suggest that T2DM is associated with an increased incidence and mortality from many cancers. The purpose of this review is to discuss the links between diabetes and cancer, the effects of various antidiabetic medications on cancer incidence and mortality, and the effects of anticancer therapies on diabetes. DesignThis study is a review of preclinical and clinical data regarding the effects of antidiabetic medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 90 publications
4
158
0
11
Order By: Relevance
“…Számos elmélet született, hogy e megfigyelés hátterében különböző, a T2DM-et befolyásoló, illetve a betegség miatt kialakuló tényezők állhatnak, mint például a hyperglykaemia, az inzulinrezisztencia, a hyperinsulinaemia, a magasabb széruminzu-lin-szerű növekedési faktor-1 (IGF1) koncentrációja, a folyamatos gyulladásos állapotok miatti magasabb citokinkoncentrációk, az oxidatív stressz, a dyslipidaemia vagy a fokozott thrombocytaaktiváció [20][21][22][23][24][25]. A T2DM-betegek kezelése során alkalmazott különböző antidiabetikumok tumorokkal szembeni védő-vagy ép-pen azok növekedését serkentő hatása jelenleg is számos klinikai gyógyszervizsgálat tárgyát képezi [21]. A legtöbb vizsgálat -a feltételezett tumorvédő hatása miatta metforminnal kapcsolatban folyt/folyik [26,27].…”
Section: Eredeti Közleményunclassified
“…Számos elmélet született, hogy e megfigyelés hátterében különböző, a T2DM-et befolyásoló, illetve a betegség miatt kialakuló tényezők állhatnak, mint például a hyperglykaemia, az inzulinrezisztencia, a hyperinsulinaemia, a magasabb széruminzu-lin-szerű növekedési faktor-1 (IGF1) koncentrációja, a folyamatos gyulladásos állapotok miatti magasabb citokinkoncentrációk, az oxidatív stressz, a dyslipidaemia vagy a fokozott thrombocytaaktiváció [20][21][22][23][24][25]. A T2DM-betegek kezelése során alkalmazott különböző antidiabetikumok tumorokkal szembeni védő-vagy ép-pen azok növekedését serkentő hatása jelenleg is számos klinikai gyógyszervizsgálat tárgyát képezi [21]. A legtöbb vizsgálat -a feltételezett tumorvédő hatása miatta metforminnal kapcsolatban folyt/folyik [26,27].…”
Section: Eredeti Közleményunclassified
“…Targeted inhibitors for components of the IR signaling cascade have been the focus of many pre-clinical and clinical studies (Shlomai et al 2016). However, several of these agents, in particular inhibitors of the PI3K/Akt/mTOR pathway and IGF-1R-targeted therapies, have been associated with high rates of metabolic abnormalities in clinical trials (Shlomai et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, several of these agents, in particular inhibitors of the PI3K/Akt/mTOR pathway and IGF-1R-targeted therapies, have been associated with high rates of metabolic abnormalities in clinical trials (Shlomai et al 2016). We have previously shown that mTOR inhibition with rapamycin, significantly suppressed tumor growth in the presence of hyperinsulinemia, however it also markedly impaired glucose and lipid homeostasis and altered body composition (Fierz et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these agents target signalling pathways that influence cellular glucose metabolism, and increasing amounts of data demonstrate that TKI therapy can result in either elevated or decreased blood glucose levels, depending on the agent used and the clinical context 2,3 (TABLE 1). In some settings, hyperglycaemia has been reported as a common adverse effect of TKI therapy 4 .…”
mentioning
confidence: 99%